KONSEP PEMIKIRAN MEHDI GOLSHANI : AGAMA DAN SAINS - Moh. Ainul Yakin; Nur Aimmatul Aula; Helmi Syaifuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
Religion and science are forces capable of transforming human life. Both try to direct and provide welfare for mankind. With their advantages and limitations, these two subject figures are proven to have made a real contribution to improving the standard of human life. Mehdi Golshani is one of the philosopher who expressed his opinion on religion and science. The purpose of this study was to determine the concept of religious and scientific thought according to Mehdi Golshani. The research method used is literature / literacy. By examining the contents of the book, the substance of the discussion and the focus of the character's study and thoughts. The object is in the form of several research journal books which contain Mehdi Golshani's thoughts on religion and science. The results in the context of Mehdi Golshani's thought are used as a way to solve all natural phenomena, where the climax of all of them is to internalize self-awareness of the existence and power of God of the universe. The natural phenomenon that exists in human life is not just a coincidence, nor does it occur in the middle of nowhere. Keywords: Religion, Science, Mehdi Golshani. Agama dan sains adalah kekuatan yang mampu mentransformasi kehidupan manusia. Keduanya berusaha mengarahkan dan memberikan kesejahteraan bagi umat manusia. Dengan kelebihan dan keterbatasannya, kedua subjek ini terbukti memberikan kontribusi nyata dalam meningkatkan taraf hidup manusia. Mehdi Golshani adalah salah satu filsuf yang mengutarakan pendapatnya tentang agama dan sains. Tujuan penelitian ini adalah untuk mengetahui konsep pemikiran religius dan ilmiah menurut Mehdi Golshani. Metode penelitian yang digunakan adalah studi pustaka / literasi. Dengan menelaah isi buku, substansi pembahasan serta fokus kajian dan pemikiran tokoh. Objeknya berupa beberapa buku jurnal penelitian yang memuat pemikiran Mahdi Golshani tentang agama dan sains. Hasil pemikiran dalam konteks pemikiran Mehdi Golshani digunakan sebagai cara untuk menyelesaikan semua fenomena alam, dimana puncaknya semuanya adalah menginternalisasi kesadaran diri akan keberadaan dan kekuatan Tuhan semesta alam. Fenomena alam yang ada dalam kehidupan manusia bukan hanya kebetulan, juga tidak terjadi di antah berantah.